Zonal Similarity of Long‐Term Changes and Seasonal Cycles of Baseline Ozone at Northern Midlatitudes. Issue 13 (3rd July 2020) - Parrish, David D.; Derwent, Richard G.; Steinbrecht, Wolfgang; Stübi, René; Van Malderen, Roeland; Steinbacher, Martin; Trickl, Thomas; Ries, Ludwig; Xu, Xiaobin
Abstract: The lifetime of ozone in the troposphere is approximately 3 weeks. Prevailing westerly winds at northern midlatitudes can transport air around the globe in that time. Hence, within these latitudes zonal similarity is expected in long‐term changes and seasonal cycles of concentrations of baseline ozone. We quantify the degree of zonal similarity by examining eight in situ baseline ozone data sets near the west coasts of North America and Europe, that is, upwind of those continents and downwind of the Pacific and Atlantic Oceans, where the impacts of local and regional ozone sources have been largely mixed into the troposphere, giving the best‐defined baseline ozone signature. Zonal similarity is found in both long‐term changes and seasonal cycles. The decades‐long increase in Northern Hemisphere, midlatitude baseline mixing ratios (average ~0.60 ppb year −1 from 1980–2000), has ended, with a maximum reached in the mid‐2000s, followed by slow decrease (average = −0.09 ± 0.08 ppb year −1 from 2000 to the present). The year of the ozone maximum exhibits little if any statistically significant difference with location, altitude, or season. The ozone seasonal cycle differs markedly between sea‐level coastal stations representative of the marine boundary layer and the free troposphere sampled at elevated sites and by sondes and aircraft. However, within each of these broad tropospheric layers, the seasonal cycles are similar at all locations. Vertical profiles of the parameters that define the long‐term trends and the seasonal cycle are also similar between North America and Europe. Plain Language Summary: Ozone in the lower atmosphere (i.e., the troposphere) plays important roles in atmospheric chemistry, air pollution, and climate change. Ozone has a wide variety of sources and sinks that vary temporally and spatially, which complicate our efforts to fully understand ozone's temporal and spatial distribution. Strong sources (primarily man‐made and natural) and sinks of ozone are located in the lower troposphere (i.e., the boundary layer), and input of ozone from the stratosphere is a strong source to the upper troposphere. Here we use long‐term records (~2 decades or more) of measured ozone concentrations at relatively remote locations in the northern midlatitudes (where the majority of man‐made ozone sources are located) to quantify as accurately and precisely as possible ozone's long‐term changes and seasonal cycles. Consistent with the ~3‐week lifetime of ozone in the troposphere, we find substantial similarity in these temporal variations throughout this latitude band. From the start of the measurements in the late 1970s, these concentrations increased until a maximum was reached in the mid‐2000s, followed by slowly decreasing concentrations. Decreasing ozone concentrations in the background troposphere is good news from the perspective of ozone's contributions to urban and regional air pollution and climate change. Key Points: Long‐term changes and seasonal cycles of lower troposphere baseline ozone are similar throughout northern midlatitudes At northern midlatitudes baseline ozone increased before 2000, but that increase ended, and average concentrations have since decreased The year of the baseline ozone maximum (~2006) does not vary significantly with location, altitude, or season